1979
DOI: 10.1080/01635587909513625
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary carbohydrate on the incidence of mammary tumors induced in rats by 7, 12‐dimethylbenz[α] anthracene

Abstract: Groups of 20 female Sprague-Dawley rats were given a single oral 5 mg dose of 7,12-dimethylbenz(a)anthracene at 50 days of age, and one week later were transferred from a Purina Chow diet to purified diets containing 68% by weight of sugar (dextrose or sucrose) or starch (wheat, rice or potato starch) and 5% by weight of fat. Sucrose and wheat starch were also fed at a level of 49% in a diet containing 20% fat. Rats fed the sugar diets developed significantly more mammary tumors than those fed the starch diets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Studies in rats have found an increased incidence of 7,12-dimethylbenz(a)anthracene-induced breast cancer in animals fed diets high in vegetable fat [ 14] and sugar [15]. There are several points in the current study that are of particular interest.…”
Section: Nutrition and Cancer©1981mentioning
confidence: 73%
“…Studies in rats have found an increased incidence of 7,12-dimethylbenz(a)anthracene-induced breast cancer in animals fed diets high in vegetable fat [ 14] and sugar [15]. There are several points in the current study that are of particular interest.…”
Section: Nutrition and Cancer©1981mentioning
confidence: 73%
“…In 1979, Hoehn et al demonstrated that after injection of 7,12-dimethylbenz(α)-anthracene (DMBA), rats that consumed sucrose/dextrose diets developed more mammary tumors than rats fed with starch (6). However using the same rat model, Klurfeld and colleagues observed opposite results that consumption of a corn starch diet was associated with the most palpable and largest tumors than rats fed with sucrose or lactose diets (7).…”
Section: Introductionmentioning
confidence: 99%
“…This was observed at both high and low levels of dietary fat. 23 Like the epidemiological data, however, the results of experiments with animals Indicated that dietary carbohydrate had less influence on mammary carcinogenesis than did dietary fat.…”
Section: Effects Of Dietary Components Other Than Fat On Mammary Carcmentioning
confidence: 86%